Nutritive Values of Rice Straw Fermentation Used Carbon Sources on Different Level with Various of Inoculant Levels Aspergillus niger and Lactobacillus plantarum - Saputro, R. Agus Tri Widodo (2015)
ABSTRACT: Utilization of agricultural waste products (rice straw) as the basic feed into the strategic thing to be developed to meet the needs of fibrous feed for cattle. Cellulolytic microbes and lactic acid bacteria are sources of inoculum that can improve the quality of rice straw as feed fibrous base. The study was conducted with the aim to obtain the appropriate carbon source for the growth of Aspergillus niger and Lactobacillus plantarum. The microbial are grown with solid and semi-solid method. The sources of carbon treatment were given two kinds of substrates,namely molasses and rice bran. The treatment of Aspergillus niger with a level of 0.5, 10, and 15%. Administration of Lactobacillus plantarum was 10% in each treatment. Fermentation is carried out for 21 days. The variables were observed in this study were pH, lactic acid, DM,OM, CP, CF, NDF, ADF, and TDN. Data were analyzed using analysis of variance completely randomized design (CRD) unidirectional pattern and factorial pattern (2 x 4), if there is a real effect, then it was followed by DMRT (Duncan’s Multiple Range Test). The results showed that the best substrate was molasses and Aspergillus niger at best level of 15%. It was based on the value of the lowest crude fiber and lactic acid produced the highest (P<0.05). It was concluded that the use of Aspergillus niger and Lactobacillus plantarum were best for fermented rice straw; the dry matter of Aspergillus niger was 15% and Lactobacillus plantarum was 10%.